A Relativistic Compact Stellar Model of Anisotropic Quark Matter Mixed with Dark Energy. (8th November 2021) - Grammenos, Theophanes; Rahaman, Farook; Ray, Saibal; Deb, Debabrata; Chowdhury, Sourav Roy
Abstract : The possibility of strange stars mixed with dark energy to be one of the candidates for dark energy stars is the main issue of the present study. Our investigation shows that quark matter atcs as dark energy after a certain yet unknown critical condition inside the quark stars. Our proposed model reveals that strange stars mixed with dark energy feature a physically acceptable stable model and mimic characteristics of dark energy stars. The plausible connections are shown through the mass-radius relation as well as the entropy and temperature. We particularly note that a two-fluid distribution is a major reason for the anisotropic nature of the spherical stellar system.